PKK Creativity in Increasing MSMEs Sales Turnover in Medan Sunggal - Siregar, Epi supriyani; Siregar, Budi Alamsyah; Suma, Dewi; Dewi, Ratna Sari; Nurul Dalimunte (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to develop PKK creativity in increasing MSME sales turnover in Medan Sunggal. In Increasing PKK Creativity in improving MSMEs in the Medan Sunggal PKK environment to support government programs in creating entrepreneurs and improving their quality. Globally, this training aims to increase entrepreneurial abilities and improve the quality of management and financial governance for micro, small and medium enterprises. (MSMEs) can operate independently. Planning, implementation, and evaluation are the three stages that go through to complete this work. Provided two meetings which were attended by 25 participants from MSME actors in the environment. PKK Medan is single. The results and discussion of this activity teach MSME players about entrepreneurship education, effective marketing strategies, and simple financial management. They also learn about the various financing schemes they can use.